Preparation method based on oxygen-free copper surface nanocrystallization interface structure

By constructing a layer of Ag, Au, and Cu nanoparticles on the surface of oxygen-free copper, the problems of insufficient nanoparticle binding force and uncontrollable interface structure were solved, efficient and low-cost nano-interface preparation was achieved, and the chip sintering quality and stability were improved.

CN120767196APending Publication Date: 2025-10-10NANTONG WINSPOWER SEMICON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510744372.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-05
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The existing nano-interface design of oxygen-free copper substrates has problems such as insufficient bonding between nanoparticles and the substrate and uncontrollable interface structure. Nanoparticles generated by traditional methods are easy to fall off, and the process is complex and costly.

Method used

Ag, Au, and Cu nanoparticle layers are generated on the oxygen-free copper surface by chemical in situ growth, including pretreatment, chemical reaction, and post-treatment steps. Different reducing agents and salt solutions are used to construct the nanoparticle layer on the oxygen-free copper surface to optimize the size and distribution of the particles.

Benefits of technology

The uniform deposition and high adhesion of the nanoparticle layer on the oxygen-free copper surface are achieved, which improves the uniformity and high-temperature stability of the chip sintering interface, reduces the preparation cost, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120767196A_ABST
    Figure CN120767196A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a surface nanocrystallization interface structure based on oxygen-free copper, and the preparation method comprises the following specific steps: S1, pretreatment: removing surface oxides and impurities, then washing with deionized water, and blow-drying with nitrogen; s2, preparing an Ag nano-particle layer on the surface of the oxygen-free copper by using a chemical reduction method; the Au nanoparticle layer is prepared on the surface of the oxygen-free copper by using a chemical reduction method; the Cu nano-particle layer is prepared on the surface of the oxygen-free copper by using a complexing reduction method; and S3, post-treatment: after the reaction is completed, washing with deionized water and blow-drying with nitrogen, Ag, Au and Cu nanoparticle interface layers are respectively constructed on the oxygen-free copper surface, the microstructure of a chip sintering interface is effectively improved, the sintering quality is improved, and the development of a microelectronic technology is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of microelectronic packaging materials, and in particular relates to a preparation method based on a nanometer interface structure on the surface of oxygen-free copper. Background Art

[0002] With the increasing density and miniaturization of integrated circuits, chip packaging technology has increasingly stringent requirements on the performance of interface materials. Traditional chip sintering processes mostly use pure copper or silver-plated copper substrates, which have problems such as high interface contact resistance and uneven thermal stress distribution. In recent years, interface nano-crystallization technology has shown great potential in improving material interface performance due to its unique surface effects and quantum effects. For example, metal nanoparticles (such as Ag, Au, and Cu) can significantly improve the bonding strength and thermal management efficiency between the chip and the substrate by increasing the interface contact area, lowering the melting point (such as the low-temperature sintering characteristics of nanosilver), and optimizing the electron transmission path.

[0003] In existing technologies, the preparation of metal nanoparticles often relies on electrochemical deposition or physical vapor deposition, which are complex and costly. For example, electrochemical methods require specialized equipment and carry the risk of electrolyte contamination. The design of nanostructured interfaces for oxygen-free copper substrates still faces the following challenges: 1. Insufficient bonding between nanoparticles and the substrate: Nanoparticles generated by traditional methods are prone to detachment, affecting interface stability; 2. Uncontrollable interface structure: The size, morphology, and distribution density of the nanoparticles must be precisely controlled to meet chip sintering requirements. Summary of the Invention

[0004] Purpose of the invention: The purpose of the present invention is to address the deficiencies in the prior art and provide a method for preparing a nanostructured surface of oxygen-free copper.

[0005] A nanoparticle layer is generated on the surface of the substrate by chemical in-situ growth, wherein the nanoparticle layer includes an Ag nanoparticle layer, an Au nanoparticle layer, and a Cu nanoparticle layer. The specific steps include: S1: Pretreatment, remove surface oxides and impurities, then rinse with deionized water and dry with nitrogen. Specifically includes the following steps: S11: Raw material preparation, including oxygen-free copper sheet, acetone, ethanol, dilute sulfuric acid, and deionized water.

[0006] S12: Surface pretreatment: immerse the oxygen-free copper sheet in acetone, ethanol, and deionized water in sequence, and ultrasonically clean for 10 minutes: S13: Remove surface oxides and impurities, rinse with deionized water, and blow dry with nitrogen; S14: Soak in 5% dilute sulfuric acid solution for 10 minutes to form a micron-scale rough surface to enhance the adhesion of nanoparticles.

[0007] S2: chemical reaction; The Ag nanoparticle layer is prepared on the oxygen-free copper surface by chemical reduction method, which specifically includes the following steps: S211: placing oxygen-free copper in a solution containing Ag salt; S212: adding reducing agent and dispersant; S213: reacting at a set temperature to reduce Ag ions to Ag nanoparticles, which are uniformly deposited on the surface of oxygen-free copper; The Au nanoparticle layer is prepared on the oxygen-free copper surface by chemical reduction method, which specifically includes the following steps: S221: placing oxygen-free copper in a solution containing Au salt; S222: adding a reducing agent; S223: Room temperature reaction, where the copper substrate acts as a reducing agent to displace Au nanoparticles, and the distribution density is precisely controlled by adding dilute hydrochloric acid solution; The Cu nanoparticle layer is prepared on the oxygen-free copper surface using a complex reduction method, which specifically includes the following steps: S231: placing oxygen-free copper in a solution containing a Cu salt; S232: adding a complexing agent and a reducing agent; S233: reacting at a set temperature to reduce Cu ions to Cu nanoparticles, which are uniformly deposited on the oxygen-free copper surface; S3: Post-treatment: After the reaction is complete, rinse with deionized water and blow dry with nitrogen.

[0008] A further improvement of the present invention is that the Ag nanoparticle layer, the Au nanoparticle layer, and the Cu nanoparticle layer are constructed separately on the surface of the oxygen-free copper.

[0009] A further improvement of the present invention is that when constructing the Ag nanoparticle layer, the raw materials in step S11 also include silver nitrate, sodium citrate, and polyvinyl pyrrolidone; the Ag salt in step S211 is a 0.1M silver nitrate solution; the reducing agent and dispersant in step S212 are a 0.5M sodium citrate solution, and the 0.5M sodium citrate solution is mixed with a 0.2M polyvinyl pyrrolidone solution.

[0010] A further improvement of the present invention is that when constructing the Au nanoparticle layer, the raw materials in step S11 also include chloroauric acid, ascorbic acid, and hydrochloric acid; the Au salt in step S221 is a solution of 0.05M chloroauric acid and 0.1M ascorbic acid; the reducing agent in step S222 is a copper substrate, and the particle size of the Au nanoparticles is controlled to be 10 to 30 nm.

[0011] A further improvement of the present invention is that when constructing the Cu nanoparticle layer, the raw materials in step S11 also include copper sulfate, ethylenediaminetetraacetic acid, and ascorbic acid; the Cu salt in step S231 is a 0.2M copper sulfate solution, and the reducing agent in step S232 is 0.3M ascorbic acid. By controlling the molar ratio of ethylenediaminetetraacetic acid to Cu²⁺, Cu nanoparticles are obtained, and the particle size of the Cu nanoparticles is 50 to 80 nm.

[0012] A further improvement of the present invention is that in step S213, the temperature is set to 50-70°C.

[0013] A further improvement of the present invention is that in step S223, the pH value of the dilute hydrochloric acid solution is 3-4.

[0014] A further improvement of the present invention is that in step S233, the temperature is set to 40-50°C.

[0015] Compared with the prior art, the preparation method of the nanostructured interface structure on the surface of oxygen-free copper provided by the present invention achieves at least the following beneficial effects: The present invention provides a technical solution for preparing an Ag, Au, and Cu nanoparticle interface layer on an oxygen-free copper surface by a purely chemical method. A reducing agent is added to a solution containing Ag, Au, and Cu salts to achieve the preparation of the nanoparticle layer. This preparation method is convenient and efficient in operation, suitable for large-scale production, effectively improves the microstructure of the chip sintering interface, improves the sintering quality, promotes the development of microelectronics technology, and solves the problems of complex processes and high costs of existing physical or electrochemical methods. At the same time, it improves the uniformity, adhesion, and high-temperature stability of the interface nanostructure, meeting the requirements of chip sintering for interface thermal conductivity and mechanical strength. By optimizing the chemical reduction process, Ag, Au, and Cu nanoparticle interface layers are respectively constructed on the oxygen-free copper surface. Combined with substrate pretreatment and chemical reduction technology, low-cost and high-consistency preparation of high-performance chip sintering interfaces is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 Flowchart of the present invention. DETAILED DESCRIPTION

[0017] Various exemplary embodiments of the present invention will now be described in detail. It should be noted that unless otherwise specifically stated, the relative arrangement of components and steps, numerical expressions, and values ​​set forth in these embodiments do not limit the scope of the present invention. The following description of at least one exemplary embodiment is merely illustrative in nature and is in no way intended to limit the invention, its application, or uses.

[0018] Techniques, methods, and apparatus known to those skilled in the art may not be discussed in detail, but where appropriate, such techniques, methods, and apparatus should be considered part of the specification. In all examples shown and discussed herein, any specific values ​​should be interpreted as merely exemplary and not limiting. Therefore, other examples of the exemplary embodiments may have different values.

[0019] See Figure 1 Based on the preparation method of the nanostructured interface structure on the surface of oxygen-free copper, a nanoparticle layer is generated on the surface of the substrate by chemical in-situ growth. The nanoparticle layer includes an Ag nanoparticle layer, an Au nanoparticle layer, and a Cu nanoparticle layer. The specific steps include: S1: Pretreatment, remove surface oxides and impurities, then rinse with deionized water and dry with nitrogen. Specifically includes the following steps: S11: Raw material preparation, including oxygen-free copper sheet, acetone, ethanol, dilute sulfuric acid, and deionized water.

[0020] S12: Surface pretreatment: immerse the oxygen-free copper sheet in acetone, ethanol, and deionized water in sequence, and ultrasonically clean for 10 minutes: S13: Remove surface oxides and impurities, rinse with deionized water, and blow dry with nitrogen; S14: Soak in 5% dilute sulfuric acid solution for 10 minutes to form a micron-scale rough surface to enhance the adhesion of nanoparticles.

[0021] S2: chemical reaction; The Ag nanoparticle layer is prepared on the oxygen-free copper surface by chemical reduction method, which specifically includes the following steps: S211: placing oxygen-free copper in a solution containing Ag salt; S212: adding reducing agent and dispersant; S213: reacting at a set temperature to reduce Ag ions to Ag nanoparticles, which are uniformly deposited on the surface of oxygen-free copper; The Au nanoparticle layer is prepared on the oxygen-free copper surface by chemical reduction method, which specifically includes the following steps: S221: placing oxygen-free copper in a solution containing Au salt; S222: adding a reducing agent; S223: Room temperature reaction, where the copper substrate acts as a reducing agent to displace Au nanoparticles, and the distribution density is precisely controlled by adding dilute hydrochloric acid solution; The Cu nanoparticle layer is prepared on the oxygen-free copper surface using a complex reduction method, which specifically includes the following steps: S231: placing oxygen-free copper in a solution containing a Cu salt; S232: adding a complexing agent and a reducing agent; S233: reacting at a set temperature to reduce Cu ions to Cu nanoparticles, which are uniformly deposited on the oxygen-free copper surface; S3: Post-treatment: After the reaction is complete, rinse with deionized water and blow dry with nitrogen.

[0022] A further improvement of the present invention is that the Ag nanoparticle layer, the Au nanoparticle layer, and the Cu nanoparticle layer are constructed separately on the surface of the oxygen-free copper.

[0023] A further improvement of the present invention is that when constructing the Ag nanoparticle layer, the raw materials in step S11 also include silver nitrate, sodium citrate, and polyvinyl pyrrolidone; the Ag salt in step S211 is a 0.1M silver nitrate solution; the reducing agent and dispersant in step S212 are a 0.5M sodium citrate solution, and the 0.5M sodium citrate solution is mixed with a 0.2M polyvinyl pyrrolidone solution.

[0024] A further improvement of the present invention is that when constructing the Au nanoparticle layer, the raw materials in step S11 also include chloroauric acid, ascorbic acid, and hydrochloric acid; the Au salt in step S221 is a solution of 0.05M chloroauric acid and 0.1M ascorbic acid; the reducing agent in step S222 is a copper substrate, and the particle size of the Au nanoparticles is controlled to be 10 to 30 nm.

[0025] A further improvement of the present invention is that when constructing the Cu nanoparticle layer, the raw materials in step S11 also include copper sulfate, ethylenediaminetetraacetic acid, and ascorbic acid; the Cu salt in step S231 is a 0.2M copper sulfate solution, and the reducing agent in step S232 is 0.3M ascorbic acid. By controlling the molar ratio of ethylenediaminetetraacetic acid to Cu²⁺, Cu nanoparticles are obtained, and the particle size of the Cu nanoparticles is 50 to 80 nm.

[0026] A further improvement of the present invention is that in step S213, the temperature is set to 50-70°C.

[0027] A further improvement of the present invention is that in step S223, the pH value of the dilute hydrochloric acid solution is 3-4.

[0028] A further improvement of the present invention is that in step S233, the temperature is set to 40-50°C.

[0029] Example 1: Preparation of Ag nanoparticle layer 1. Oxygen-free copper substrate pretreatment Material preparation: oxygen-free copper sheet, acetone, ethanol, dilute sulfuric acid, silver nitrate, sodium citrate, polyvinyl pyrrolidone, and deionized water.

[0030] Surface pretreatment: Immerse the oxygen-free copper sheet in acetone, ethanol, and deionized water for ultrasonic cleaning for 10 minutes to remove surface oxides and impurities, then rinse with deionized water and blow dry with nitrogen.

[0031] Acid etching treatment: Soak in 5% dilute sulfuric acid solution for 10 minutes to form a micron-level rough surface and enhance the adhesion of nanoparticles.

[0032] 2. Preparation of Ag nanoparticle layer: The pretreated copper sheet was immersed in a mixed solution containing 0.1M silver nitrate, 0.5M sodium citrate, and 0.2M polyvinylpyrrolidone (PVP) at 60°C for 30 minutes. The sodium citrate acted as a reducing agent and dispersant, while the PVP inhibited particle aggregation, forming a uniform coating of Ag nanoparticles with a particle size of 20 to 50 nm.

[0033] 3. Post-processing: After the reaction was completed, the sample was rinsed with deionized water and dried with nitrogen.

[0034] Example 2: Preparation of Au nanoparticle layer 1. Oxygen-free copper substrate pretreatment Material preparation: oxygen-free copper sheet, acetone, ethanol, dilute sulfuric acid, chloroauric acid, ascorbic acid, hydrochloric acid, and deionized water.

[0035] Surface pretreatment: Immerse the oxygen-free copper sheet in acetone, ethanol, and deionized water for ultrasonic cleaning for 10 minutes to remove surface oxides and impurities, then rinse with deionized water and blow dry with nitrogen.

[0036] Acid etching treatment: Soak in 5% dilute sulfuric acid solution for 10 minutes to form a micron-level rough surface and enhance the adhesion of nanoparticles.

[0037] 2. Preparation of Au nanoparticle layer: A copper sheet was immersed in a solution containing 0.05M chloroauric acid (HAuCl4) and 0.1M ascorbic acid for 15 minutes at room temperature. The copper substrate acted as a reducing agent, displacing Au nanoparticles with a particle size of 10 to 30 nm. The distribution density was precisely controlled by adding dilute hydrochloric acid solution, and the pH was adjusted to 3 to 4.

[0038] 3. Post-processing: After the reaction was completed, the sample was rinsed with deionized water and dried with nitrogen.

[0039] Example 3: Preparation of Cu Nanoparticle Layer 1. Oxygen-free copper substrate pretreatment Material preparation: oxygen-free copper sheet, acetone, ethanol, dilute sulfuric acid, copper sulfate, ethylenediaminetetraacetic acid, ascorbic acid, and deionized water.

[0040] Surface pretreatment: Immerse the oxygen-free copper sheet in acetone, ethanol, and deionized water for ultrasonic cleaning for 10 minutes to remove surface oxides and impurities, then rinse with deionized water and blow dry with nitrogen.

[0041] Acid etching treatment: Soak in 5% dilute sulfuric acid solution for 10 minutes to form a micron-level rough surface and enhance the adhesion of nanoparticles.

[0042] 2. Preparation of Cu nanoparticle layer: The complexation reduction method uses a copper sulfate solution (0.2M) as a precursor, ethylenediaminetetraacetic acid (EDTA) as a complexing agent, and ascorbic acid (0.3M) as a reducing agent, reacting at 45°C for 6 hours. By controlling the molar ratio of EDTA to Cu²⁺ (1:1), Cu nanocrystals with a uniform particle size (50-80nm) are obtained. No surfactant is required, and the reaction conditions are mild.

[0043] 3. Post-processing: After the reaction was completed, the sample was rinsed with deionized water and dried with nitrogen.

Claims

1. A method for preparing a nanostructured interface structure on the surface of oxygen-free copper, characterized in that: A nanoparticle layer is generated on the surface of the substrate by chemical in-situ growth, wherein the nanoparticle layer includes an Ag nanoparticle layer, an Au nanoparticle layer, and a Cu nanoparticle layer. The specific steps include: S1: Pretreatment, remove surface oxides and impurities, then rinse with deionized water and dry with nitrogen. Specifically includes the following steps: S11: preparing raw materials, including oxygen-free copper sheet, acetone, ethanol, dilute sulfuric acid, and deionized water; S12: Surface pretreatment: immerse the oxygen-free copper sheet in acetone, ethanol, and deionized water in sequence, and ultrasonically clean for 10 minutes: S13: Remove surface oxides and impurities, rinse with deionized water, and blow dry with nitrogen; S14: Soaking in 5% dilute sulfuric acid solution for 10 minutes to form a micron-scale rough surface to enhance the adhesion of nanoparticles; S2: chemical reaction; The Ag nanoparticle layer is prepared on the surface of oxygen-free copper by a chemical reduction method, which specifically includes the following steps: S211: placing oxygen-free copper in a solution containing Ag salt; S212: adding reducing agent and dispersant; S213: reacting at a set temperature to reduce Ag ions to Ag nanoparticles, which are uniformly deposited on the surface of oxygen-free copper; The Au nanoparticle layer is prepared on the surface of oxygen-free copper by a chemical reduction method, which specifically includes the following steps: S221: placing oxygen-free copper in a solution containing Au salt; S222: adding a reducing agent; S223: Room temperature reaction, where the copper substrate acts as a reducing agent to displace Au nanoparticles, and the distribution density is precisely controlled by adding dilute hydrochloric acid solution; The Cu nanoparticle layer is prepared on the surface of oxygen-free copper using a complex reduction method, which specifically includes the following steps: S231: placing oxygen-free copper in a solution containing a Cu salt; S232: adding a complexing agent and a reducing agent; S233: reacting at a set temperature to reduce Cu ions to Cu nanoparticles, which are uniformly deposited on the oxygen-free copper surface; S3: Post-treatment: After the reaction is complete, rinse with deionized water and blow dry with nitrogen.

2. The method for preparing the surface nanostructured interface of oxygen-free copper according to claim 1, wherein: The Ag nanoparticle layer, the Au nanoparticle layer, and the Cu nanoparticle layer are respectively constructed on the surface of oxygen-free copper.

3. The method for preparing the surface nanostructured interface of oxygen-free copper according to claim 2, wherein: When constructing the Ag nanoparticle layer, the raw materials in step S11 also include silver nitrate, sodium citrate, and polyvinyl pyrrolidone; the Ag salt in step S211 is a 0.1M silver nitrate solution; the reducing agent and dispersant in step S212 are a 0.5M sodium citrate solution, and the 0.5M sodium citrate solution is mixed with a 0.2M polyvinyl pyrrolidone solution.

4. The method for preparing the surface nanostructured interface of oxygen-free copper according to claim 2, wherein: When constructing the Au nanoparticle layer, the raw materials in step S11 also include chloroauric acid, ascorbic acid, and hydrochloric acid; the Au salt in step S221 is a solution of 0.05M chloroauric acid and 0.1M ascorbic acid; the reducing agent in step S222 is a copper substrate, and the particle size of the Au nanoparticles is controlled to be 10 to 30 nm.

5. The method for preparing the surface nanostructured interface of oxygen-free copper according to claim 2, wherein: When constructing the Cu nanoparticle layer, the raw materials in step S11 also include copper sulfate, ethylenediaminetetraacetic acid, and ascorbic acid; the Cu salt in step S231 is a 0.2M copper sulfate solution, and the reducing agent in step S232 is 0.3M ascorbic acid. By controlling the molar ratio of ethylenediaminetetraacetic acid to Cu²⁺, Cu nanoparticles are obtained, and the particle size of the Cu nanoparticles is 50 to 80 nm.

6. The method for preparing the surface nanostructured interface of oxygen-free copper according to claim 1, wherein: In step S213, the set temperature is 50-70°C.

7. The method for preparing the surface nanostructured interface of oxygen-free copper according to claim 1, wherein: In step S223, the pH value of the dilute hydrochloric acid solution is 3-4.

8. The method for preparing the surface nanostructured interface of oxygen-free copper according to claim 1, wherein: In step S233, the set temperature is 40-50°C.